1998
DOI: 10.1074/jbc.273.37.23856
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein(a) Binds via Its C-terminal Domain to the Protein Core of the Proteoglycan Decorin

Abstract: Although it is known that lipoprotein(a) (Lp(a)) binds to proteoglycans, the mechanism for this binding has not been fully elucidated. In order to shed light on this subject, we examined the interactions of decorin, a proteoglycan with a well defined protein core and a single glycosaminoglycan (GAG) chain, with Lp(a) and derivatives, namely Lp(a) deprived of apo(a), or Lp(a؊), free apo(a), and the two main proteolytic fragments, F1 and F2. By circular dichroism criteria, the decorin preparations used had the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…Because F1 and F2 are generated in vitro by the action of both NE (5) and MMP-12 on apo(a), one has to ask why only F1 was present in the plasma of the NE Ϫ/Ϫ and control mice injected intravenously with apo(a). This may be because of the fact that F2 but not F1 binds to matrix macromolecules such as fibrinogen and fibronectin (4) and as exemplified by our recent findings on the proteoglycan decorin (29). On the other hand, F1, for which no ligand has been identified thus far (30), once formed at tissue sites would be free to diffuse and return to the blood stream by a reverse flow process.…”
Section: Studies On the In Vitro Proteolytic Cleavage Of Lp(a)/apo(a)mentioning
confidence: 91%
“…Because F1 and F2 are generated in vitro by the action of both NE (5) and MMP-12 on apo(a), one has to ask why only F1 was present in the plasma of the NE Ϫ/Ϫ and control mice injected intravenously with apo(a). This may be because of the fact that F2 but not F1 binds to matrix macromolecules such as fibrinogen and fibronectin (4) and as exemplified by our recent findings on the proteoglycan decorin (29). On the other hand, F1, for which no ligand has been identified thus far (30), once formed at tissue sites would be free to diffuse and return to the blood stream by a reverse flow process.…”
Section: Studies On the In Vitro Proteolytic Cleavage Of Lp(a)/apo(a)mentioning
confidence: 91%
“…It is possible that this discrepancy derives from the use of guanidine HCl-extracted decorin in the studies mentioned above. Although it appears that proper re-folding of decorin occurs following removal of guanidine HCl, at least based on binding to collagen type I (Vogel et al, 1984) or apolipoprotein A (Klezovitch et al, 1998), it is our experience that even a simple freezing and thawing can abrogate some of the functional properties of decorin, such as interaction with the EGFR or MAP kinase activation (Csorda´s et al, 2000;Santra et al, 2000). In addition, the culture conditions of our study differed from those reported earlier (de Lange Davies et al, 2001;Kinsella et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…28 Lp(a), which is known to be a highly atherogenic lipoprotein having a protein moiety apoB100 disulfide, binds to proteoglycans. 29 Degradation of endothelial heparan sulfate proteoglycan by homocysteine is considered to cause a loss of ability to protect the endothelial cell surface from oxidative stress. 30 Previous studies have shown that differences in expression of the proteoglycan of the arterial wall affects the subendothelial retention of atherogenic lipoproteins, including remnant particles.…”
Section: Discussionmentioning
confidence: 99%